Effect of shot peening process on the fatigue life of shot peened low alloy steel - Trung, Pham Quang (2019)
Shot peening is well known as a surface deformation process which can induce compressive residual stresses into the subsurface of materials in order to improve the fatigue life. In this paper, the effects of the process conditions for both single and double shot peening on the fatigue life of AISI 4340 low alloy steel is investigated. The fatigue tests revealed that the shot peening process could significantly enhance the fatigue life of the treated components. However, a side effect of the process was an increase in surface roughness which was more prevalent under higher peening pressures and led to a reduction in the fatigue life. Therefore, to maximize the performance of the process, the peening parameters need to be carefully selected. Microstructure analysis of the shot peened parts indicated that the nucleation cracks or initiation cracks occurred in the subsurface at depths of 10–20 μm in the case of as-received samples but moved up to the free surface for the shot peened parts.